2019
DOI: 10.1017/ice.2018.336
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic stewardship of C. difficile testing: a quasi-experimental antimicrobial stewardship study

Abstract: Objective:We evaluated whether a diagnostic stewardship initiative consisting of ASP preauthorization paired with education could reduce false-positive hospital-onset (HO) Clostridioides difficile infection (CDI).Design:Single center, quasi-experimental study.Setting:Tertiary academic medical center in Chicago, Illinois.Patients:Adult inpatients were included in the intervention if they were admitted between October 1, 2016, and April 30, 2018, and were eligible for C. difficile preauthorization review. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 17 publications
1
23
0
Order By: Relevance
“…Christensen and colleagues performed a quasi-experimental retrospective, single-center study evaluating ASP-led education and prior authorization on C. difficile NAATs [ 15 ]. The study had a pre-intervention period from January 2014 to September 2016 and a postintervention period from October 2016 to April 2018.…”
Section: Resultsmentioning
confidence: 99%
“…Christensen and colleagues performed a quasi-experimental retrospective, single-center study evaluating ASP-led education and prior authorization on C. difficile NAATs [ 15 ]. The study had a pre-intervention period from January 2014 to September 2016 and a postintervention period from October 2016 to April 2018.…”
Section: Resultsmentioning
confidence: 99%
“…Our study is not novel in its outcomes; other centers have also demonstrated reductions in C. difficile testing and HO-CDI rates with diagnostic stewardship processes. [11][12][13][14] However, we developed a novel model that was similarly effective and easily integrated into existing resources and infrastructure. Existing models described in the literature were not felt to be an appropriate fit for our institution for several reasons.…”
Section: Discussionmentioning
confidence: 99%
“…First, 2 centers utilized a model whereby once or twice daily review of batched orders was performed. 13,14 Recommendations were made to the primary team to discontinue the order if testing was deemed inappropriate. This model was not considered tenable at our institution because testing was not batched; also, concerns were expressed regarding the condensed workload at the point of review.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the results of other studies in Canada, the US, and Iran the rates of CDI and MDR positive cases are decreased significantly in our patients (P = 0.004 & 0.011) respectively. (5,23,28).…”
Section: Discussionmentioning
confidence: 99%